Pengaruh Corporate Social Responsibility, Enterprise Risk Management dan Dewan Komisaris Terhadap Nilai Perusahaan - Aliandra, Mohammad Rafly; Nauli, Emma Saur (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to examine the influence of Corporate Social Responsibility (CSR), Enterprise Risk Management (ERM), and the Board of Commissioners on Firm Value. The sample used in this study consists of real estate and property sector companies listed on the Indonesia Stock Exchange for the period 2019-2022, totaling 38 companies with 152 observations. The analysis results show that: Corporate Social Responsibility has a positive effect on Firm Value, consistent with the studies by Desita et al. (2022) and Nyoman & Dodik (2022). Enterprise Risk Management has a positive effect on Firm Value, in line with the studies by Irdawati et al. (2022) and Rakha Magistra et al. (2020). The Board of Commissioners has no influence effect on Firm Value, supporting the findings of Khoirunnisa (2022). These results indicate that the implementation of CSR, ERM, can enhance the Firm Value and Board of Commissioners cannot enhance the Firm Value in the real estate and property sector in Indonesia.